Case of rheumatic heart disease and severe mitral stenosis, managed by balloon mitral valvuloplasty in pregnancy (Indian Journal of Case Reports, 2024)
Mitral stenosis (MS) is a progressive situation caused by obstruction of blood flow across the mitral valve from the left atrium to the left ventricle. It is one of the most common valvular heart lesions found during pregnancy. The chances of significant maternal and fetal morbidity and mortality are more in the case of severe MS. Balloon mitral valvuloplasty (BMV) is a life-saving procedure in pregnancy instead of surgical correction. We are presenting the case of a 24-week pregnant woman with severe MS. She developed pulmonary edema and had undergone successful BMV which allowed her to tolerate her pregnancy decently. It leads to a decrease in the left atrial pressure as well as pulmonary arterial pressure. The patient underwent normal delivery uneventfully. Antibiotics were used with proper consultation and the patient was treated conservatively with excellent maternal and fetal outcomes. BMV is turns out to be a life-saving therapy for severe MS complicated by pulmonary edema.